Thermodynamical Properties of Transition Metal Diborides under Pressure - Ahmad Wani, Tanveer; Singh, Pankaj (Asian Journal of Chemistry, 2011)
Most of the metal diborides have the AlB2 structure in which layers of close-packed metal atoms alternate with planes of B atoms with a graphite-like geometric structure. Although the structures of the diborides are unique, their physical properties are somewhat similar to those of nitrides and carbides. They are extremely hard and have very high melting points. They are attractive for the same types of applications as other hard, refractory materials, such as in composites and in hard coatings traditional applications of such materials are based on their interesting combination of mechanical and transport properties. Thus, in order to extend our present understanding regarding the behaviour of these materials to external influences as well as for the future technological developments, the proposal aims to calculate the thermodynamic properties of various transition metal diborides under pressure using the quasi harmonic Debye model.